The Value of Neutrophil-to-Lymphocyte Ratio in Predicting Mortality After Transjugular Intrahepatic Portosystemic Shunt Placement - Tang HH; Zhou LF; Wang CX; Zha Y; Fan C; Zhong BY; Zhu XL; Wang WD (Dove Medical Press, 2024)
Hao-Huan Tang,1,* Lin-Feng Zhou,2,3,* Chun-Xin Wang,4,* Yang Zha,4 Chen Fan,1 Bin-Yan Zhong,2 Xiao-Li Zhu,2 Wei-Dong Wang1 1Department of Interventional Radiology, The Affiliated Wuxi People's Hospital of Nanjing Medical University, Wuxi People's Hospital, Wuxi Medical Center, Nanjing Medical University, Wuxi, 214023, People's Republic of China; 2Department of Interventional Radiology, The First Affiliated Hospital of Soochow University, Suzhou, 215006, People's Republic of China; 3Department of Radiology, Hubei Cancer Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430079, People's Republic of China; 4Department of Radiology, The Affiliated Wuxi People's Hospital of Nanjing Medical University, Wuxi People's Hospital, Wuxi Medical Center, Nanjing Medical University, Wuxi, 214023, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiao-Li Zhu, The First Affiliated Hospital of Soochow University, No. 188, Shizi Street, Suzhou, 215006, People's Republic of China, Tel/Fax +86 512 67780375, Email zhuxiaoli90@163.com Wei-Dong Wang, The Affiliated Wuxi People's Hospital of Nanjing Medical University, Wuxi People's Hospital, Wuxi Medical Center, Nanjing, No. 299, Qingyang Road, Medical University, Wuxi, 214023, People's Republic of China, Tel/Fax +86 510 85350121, Email wdoc@sina.comBackground and Aims: The objective of this study was to investigate the effect of neutrophil-to-lymphocyte ratio (NLR) on the survival of cirrhotic patients with esophagogastric variceal bleeding (EGVB) treated with transjugular intrahepatic portosystemic shunt (TIPS).Methods: A total of 293 patients treated with TIPS were included. The receiver operator characteristic curve (ROC) was used to calculate the optimal cut-off values of parameters such as NLR. The Kaplan-Meier curve and Cox proportional risk model were used to evaluate the effects of NLR and other variables on 2-year all-cause mortality.Results: The area under the ROC for NLR was 0.634, with an optimal cutoff value of 4.9. Two-year mortality rates for patients with high (≥ 4.9) and low (< 4.9) NLR were 22.1% and 9.3%, respectively (Log rank test: P = 0.002). After correcting for confounders, multivariate analysis demonstrated that NLR ≥ 4.9 (HR = 2.741, 95% CI 1.467- 5.121, P = 0.002), age ≥ 63 (HR = 3.403, 95% CI 1.835- 6.310, P < 0.001), and gender (male) (HR = 2.842, 95% CI 1.366- 5.912, P = 0.001) were independent risk factors for the mortality outcome. Considering the stratification of early and selective TIPS treatment, high NLR still significantly increased the risk of mortality for patients (Log rank test: P = 0.007, HR = 2.317, 95% CI 1.232- 4.356).Conclusion: NLR can help to predict survival in EGVB patients after TIPS, and the type of TIPS should also be considered in practical applications.Keywords: neutrophil-to-lymphocyte ratio, transjugular intrahepatic portosystemic shunt, esophagogastric variceal bleeding, prognostic factor